High Sensitivity Studies Using a Tandem Mass Spectrometer - Heyland, Gunter Rolf (My University, 1967)
A description of the McMaster tandem mass spectrometer is given and the usefulness of this instrument in high sensitivity applications is discussed.
The pulse characteristics of the 17 stage Allen type electron multiplier which is used on the two stage mass spectrometer were determined and possible means of achieving an improved response in counting applications are discussed.
An ion source of the crucible variety was constructed which made possible the detection of 10^-9 grams of a tin isotope. This source was used to detect sub microgram quantities of an enriched tin sample and was also used for the qualitative analysis of a sample which contained tin extracted from a reactor irradiated fuel rod.
Keywords: sensitivity, tandem, mass, spectrometer, electron